2012
DOI: 10.1371/journal.pone.0043890
|View full text |Cite
|
Sign up to set email alerts
|

Anxiogenic Effects of Developmental Bisphenol A Exposure Are Associated with Gene Expression Changes in the Juvenile Rat Amygdala and Mitigated by Soy

Abstract: Early life exposure to Bisphenol A (BPA), a component of polycarbonate plastics and epoxy resins, alters sociosexual behavior in numerous species including humans. The present study focused on the ontogeny of these behavioral effects beginning in adolescence and assessed the underlying molecular changes in the amygdala. We also explored the mitigating potential of a soy-rich diet on these endpoints. Wistar rats were exposed to BPA via drinking water (1 mg/L) from gestation through puberty, and reared on a soy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
92
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 94 publications
15
92
1
1
Order By: Relevance
“…Thus, this study showed that perinatal exposure of GEN did not affect locomotor activity or emotionality. With regard to emotionality, a previous report suggested that GEN from soy-based diets could mitigate anxiogenic-induced effects of developmental exposure to Bisphenol A (BPA) [33]. Although there was little effect of GEN itself on anxiety in our study, it could be that GEN has the ability to relieve anxiety from an already anxiogenic condition.…”
Section: Discussioncontrasting
confidence: 65%
“…Thus, this study showed that perinatal exposure of GEN did not affect locomotor activity or emotionality. With regard to emotionality, a previous report suggested that GEN from soy-based diets could mitigate anxiogenic-induced effects of developmental exposure to Bisphenol A (BPA) [33]. Although there was little effect of GEN itself on anxiety in our study, it could be that GEN has the ability to relieve anxiety from an already anxiogenic condition.…”
Section: Discussioncontrasting
confidence: 65%
“…Patisaul et al recently reported that developmental exposure to the ED Bisphenol A (BPA) results in an anxiogenic phenotype in adulthood in rats. However, this anxiogenic phenotype was mitigated if rats were provided with a soy-based diet, demonstrating a strong interaction between EDs in the environment and soy in the diet [57].…”
Section: Discussionmentioning
confidence: 99%
“…For each experiment, all Wistar rats were obtained from Charles River (Raleigh, North Carolina) and/or bred in house as indicated in humidity-and-temperature controlled rooms, each with a 12 h:12 h light, dark cycle at 25 C and 45-60% average humidity at the Biological Resource Facility at NCSU. As in our prior studies (Patisaul et al, 2012(Patisaul et al, , 2009, and in accordance with recommended practices for endocrine-disrupting chemicals (EDC) research (Hunt et al, 2009;Li et al, 2008;Richter et al, 2007), all animals were housed in conditions specifically designed to minimize unintended EDC exposure including use of glass water bottles, soy-free diet, woodchip bedding, and thoroughly washed polysulfone caging. Individual authentic standards of EH-TBB,…”
Section: Methodsmentioning
confidence: 99%